2021
DOI: 10.3390/ani11113230
|View full text |Cite
|
Sign up to set email alerts
|

Impacts from Wildfires on Livestock Health and Production: Producer Perspectives

Abstract: Wildfires are increasing in frequency and severity across the Western United States. However, there is limited information available on the impacts these fires are having on the livelihood of livestock producers and their animals. This work presents the results of a survey evaluating the direct and indirect impacts of the 2020 wildfire season on beef cattle, dairy cattle, sheep, and goat, producers in California, Oregon, and Nevada. Seventy completed surveys were collected between May and July 2021. While dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Three animal studies were included for the potential to serve as surrogate data sources for human health impacts. One study conducted an indirect assessment of food security by surveying livestock producers on wildfire‐related impacts to production and herd health (O’Hara et al., 2021 ), and another article assessed the impact of wildfire smoke on cow milk production (Beaupied et al., 2022 ). Finally, one study assessed immune and lung function in adolescent rhesus macaque monkeys exposed to ambient wildfire smoke during infancy (Black et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three animal studies were included for the potential to serve as surrogate data sources for human health impacts. One study conducted an indirect assessment of food security by surveying livestock producers on wildfire‐related impacts to production and herd health (O’Hara et al., 2021 ), and another article assessed the impact of wildfire smoke on cow milk production (Beaupied et al., 2022 ). Finally, one study assessed immune and lung function in adolescent rhesus macaque monkeys exposed to ambient wildfire smoke during infancy (Black et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies used spatial proximity to a wildfire event or evacuation perimeters as a proxy exposure method rather than assessing a specific pollutant. Seven of these studies used surveys to obtain self‐reported information on general proximity to fire events and evacuation status as an exposure metric (Haikerwal et al., 2021 ; Hyde et al., 2021 ; Masri et al., 2021 ; O’Hara et al., 2021 ; Pazderka, Brown, Agyapong, et al., 2021 ; Pazderka, Brown, McDonald‐Harker, et al., 2021 ; Rodney et al., 2021 ). Two studies utilized personal air monitors or photometers to collect particle samples as measures of personal exposures among older adult populations, one in Los Angeles, CA (Delfino et al., 2010 ) and one in Finland (Huttunen et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfires threaten the quality of life, safety, and livelihoods of producers. They threaten infrastructure, crops (Dillis et al, 2022;Zakowski et al, 2023) , and livestock (O'Hara et al, 2021). Additionally, wildfires lead to closed markets during evacuations, power outages, smoke-related illnesses, and post-traumatic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Fast spreading fire has been implicated in dramatic changes in vegetation structure and composition [1,2], which in turn can cause negative downstream effects on water [3,4] and soil conditions [5]. The sudden emission of large quantities of smoke [6] and the rapidly advancing flames of a wildfire can pose a threat to human [7,8] and non-human health [9,10]. In addition to the associated safety risks, fast-spreading fires are particularly difficult for firefighters to control [11].…”
Section: Introductionmentioning
confidence: 99%